ASSESSMENT OF THE LEVEL OF FORMATION OF MORAL QUALITIES IN PRIMARY SCHOOL STUDENTS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The article discusses the fundamentals of assessing the level of formation of moral qualities in primary school students.